Desain Perpustakaan dalam Perkembangan Zaman - St. Zulaichah (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
A library is an important feature of education system. It also plays significant roles in helping students’ improving their knowledge and skills. Most libraries are recently developing their organizations and programs in order to adopt the change in the field and attract more visitors. There have been several unique programs offered, such as mobile libraries, digital libraries, etc. All of those recent developments have the same objective that is to empower the library. These new programmes were designated according to the current trends of the library and information science.